2013
DOI: 10.1371/journal.pone.0057499
|View full text |Cite
|
Sign up to set email alerts
|

Natural Experience Modulates the Processing of Older Adult Faces in Young Adults and 3-Year-Old Children

Abstract: Just like other face dimensions, age influences the way faces are processed by adults as well as by children. However, it remains unclear under what conditions exactly such influence occurs at both ages, in that there is some mixed evidence concerning the presence of a systematic processing advantage for peer faces (own-age bias) across the lifespan. Inconsistency in the results may stem from the fact that the individual’s face representation adapts to represent the most predominant age traits of the faces pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 53 publications
(78 reference statements)
5
37
1
1
Order By: Relevance
“…This finding is consistent with the results of past studies that have found an own-age recognition advantage among young adults (Bäckman, 1991;Proietti, Pisacane, & Macchi Cassia, 2013) and with studies showing that young adults show greater neural activation in response to young relative to older faces (Ebner, He, Fichtenholtz, McCarthy, & Johnson, 2011;Wiese et al, 2008). The novelty of this work is that, in contrast to previous studies, faces were displayed within the context of complex scenes, presented with full bodies, and shown in direct competition with another face category.…”
Section: Recognition Accuracy For Young and Older Facessupporting
confidence: 92%
“…This finding is consistent with the results of past studies that have found an own-age recognition advantage among young adults (Bäckman, 1991;Proietti, Pisacane, & Macchi Cassia, 2013) and with studies showing that young adults show greater neural activation in response to young relative to older faces (Ebner, He, Fichtenholtz, McCarthy, & Johnson, 2011;Wiese et al, 2008). The novelty of this work is that, in contrast to previous studies, faces were displayed within the context of complex scenes, presented with full bodies, and shown in direct competition with another face category.…”
Section: Recognition Accuracy For Young and Older Facessupporting
confidence: 92%
“…Because the inversion effect (Yin, 1969) and the composite effect (Young, Hellawell, & Hay, 1987) are both typically used measures of perceptual expertise, since they are larger for faces and other objects of expertise than for non-face objects for which participants have not developed specific expertise (e.g., Ashworth, Vuong, Rossion, & Tarr, 2008;Diamond & Carey, 1986), these findings have been taken as evidence for a perceptual processing bias towards adult faces in adults. Developmental research has extended this evidence to children, showing that 3year-old (Macchi Cassia, Kuefner, Picozzi, & Vescovo, 2009;Macchi Cassia, Pisacane, & Gava, 2012;Proietti et al, 2013) and 6-year-old (Macchi Cassia, children, just like adults, manifest a discrimination advantage and a selective or larger face inversion effect for adult faces compared to other-age faces, including infant faces.…”
mentioning
confidence: 96%
“…Further evidence for the impact of facial age diversity on adults' and children's face processing skills comes from studies showing that when intensive exposure to individuals from a different age group than adults occurs as part of the individual's social and/or working experience, the processing bias towards adult faces is no longer observed (e.g., de Heering & Rossion, 2008;Harrison & Hole, 2009;Kuefner et al, 2010Kuefner et al, , 2008Macchi Cassia, Picozzi, Kuefner, & Casati, 2009;Proietti et al, 2013). For example, 3-year-old (Macchi Cassia, Kuefner et al, 2009) and 6-year-old children with a younger sibling, unlike those without a younger sibling, show a generalized inversion effect and comparable discrimination abilities for adult and infant faces.…”
mentioning
confidence: 99%
“…With regard to recognition, children show a similar trend to adults in terms of typically being better at recognising adult faces. Three-year-olds without specific other-age experience are more accurate at recognizing adult faces than neonate or elderly faces (Macchi Cassia, 2011; Macchi Cassia, Kuefner, Picozzi, & Vescovo, 2009a; Proietti, Pisacane, & Macchi Cassia, 2013). Similarly, 3-year-olds without an older sibling and 6-year-olds without a sibling are better at recognising adult than child faces (Macchi Cassia, Pisacane, & Gava, 2012; Macchi Cassia, Proietti, & Pisacane, 2013).…”
Section: Responding To Face Age: Preference Recognition and Categormentioning
confidence: 99%